The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16060902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA Methylation Changes and Micronuclei in Workers Exposed to a Construction Environment

Abstract: Methylation levels in tumor-suppressor genes and repetitive sequences have previously been used to study the relationship between environmental air pollution and epigenetic changes related to cancer. In this study, we measured the methylation profiles of the promoter regions CDKN2A, MLH1 and APC and the repetitive sequence LINE-1 in 59 workers exposed to the construction environment and in 49 unexposed workers. We also evaluated the micronuclei frequency and levels of trace elements in the blood of all workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
10
0
2
Order By: Relevance
“…In another study, despite no significant difference in global DNA methylation, it was possible to observe DNA methylation changes in the promoter CpG regions of genes of enzymes involved in the epigenetic regulation, DNA repair (i.e., DNMT1, HDAC4, ATM), and gene of TGF-β repressor (SKI) in blood cells of workers exposed to multi-walled carbon nanotubes (MWCNT) with respect to unexposed control individuals ( 68 ). Furthermore, workers exposed to particulate matter and polycyclic aromatic hydrocarbons exhibited, in their peripheral blood leukocytes, significantly higher average levels of methylation at the promoter of tumor-suppressor genes, such as CDKN2A, APC, and MLH1, and significant hypomethylation at the repetitive DNA sequence LINE-1 (a sequence involved in DNA folding/packaging) in comparison to unexposed workers ( 69 ).…”
Section: Nanoparticles and Epigeneticsmentioning
confidence: 99%
“…In another study, despite no significant difference in global DNA methylation, it was possible to observe DNA methylation changes in the promoter CpG regions of genes of enzymes involved in the epigenetic regulation, DNA repair (i.e., DNMT1, HDAC4, ATM), and gene of TGF-β repressor (SKI) in blood cells of workers exposed to multi-walled carbon nanotubes (MWCNT) with respect to unexposed control individuals ( 68 ). Furthermore, workers exposed to particulate matter and polycyclic aromatic hydrocarbons exhibited, in their peripheral blood leukocytes, significantly higher average levels of methylation at the promoter of tumor-suppressor genes, such as CDKN2A, APC, and MLH1, and significant hypomethylation at the repetitive DNA sequence LINE-1 (a sequence involved in DNA folding/packaging) in comparison to unexposed workers ( 69 ).…”
Section: Nanoparticles and Epigeneticsmentioning
confidence: 99%
“…Similar to our observation, Line‐1 hypomethylation in peripheral lymphocytes were associated with MN frequency among polycyclic aromatic hydrocarbon‐exposed workers (Duan et al, 2013). Another report (Silva et al, 2019) also found that Line‐1 methylation and MN frequency were negatively correlated among workers exposed to a construction environment. MN formation was reported to be induced epigenetically via the loss of DNA methylation (Luzhna et al, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…Silva et al ( 111 ) studied CDKN2A, MLH1 , and APC promoter methylation and LINE-1 as a surrogate marker of global methylation in 59 workers exposed to the construction environment and in 49 unexposed workers. They observed higher average levels of methylation for all three genes and hypomethylation of the LINE-1.…”
Section: Resultsmentioning
confidence: 99%